Study of the collection sesame samples in the Rostov region - L. P. Zbrailova; T. N. Luchkina; Е. А. Krat-Kravchenko (Зерновое хозяйство России, 2022)
From 2018 to 2020, there was studied a collection of sesame varieties of various ecological and geographical origin at the Don Experimental Station, a branch of the Federal State Budget Scientific Institution Federal Research Center VNIIMK. The research was carried out within the framework of State assignment No. 0684-2019-0013 ‘Development of new source material and identifying varieties and hybrids of oilseeds: sunflower, mustard, flax. Preservation of the gene pool of the main oilseeds’. The purpose of the current research was to study the morphobiological characteristics of sesame samples of various ecological and geographical origin, to study the growth and development of light- and dark-seeded groups, to identify samples with positive economically valuable traits. The color of sesame seeds is associated with their biochemical functions involved in protein and oil metabolism, as well as with the content of antioxidants (Chengqi et al., 2021). Studying collection samples by a set of traits, it is necessary to identify the most promising ones (Bashlakova, Sintsova, 2021). They must have high productivity, resistance to unfavorable conditions of the cultivation region. It is necessary to pay attention to a length of a vegetation period, a shape, location and capsules’ cracking. (Kalitskaya, Sinegovskaya et al., 2021). The current paper has presented the study results of sesame varieties from the VIR collection. There has been presented a comparative characteristic of light- and dark-seeded groups. There have been described the differences in the main economically valuable traits, phenological phases, and fatty acid composition. There has been established a range of variation between groups with different vegetation periods, fatty acid composition and other economically valuable traits. Phenological observations have shown that the range of variation in a vegetation period and plant height in the dark-seeded group was wider than in light-seeded samples. Productivity of the light-seeded group was 0.56–0.62 t/ha, which was 0.13–0.24 t/ha higher than the dark-seeded samples with 0.32–0.49 t/ha. The range of variation within the groups was 0.16 t/ha for light-seeded and 0.17 t/ha for dark-seeded samples. The oil content in the light-seeded group is also higher than the samples with dark seeds on 0.8–1.2 %, the variation range within the light-seeded group was 2.9 % and 2.5 % within the dark-seeded group. 1000-seed weight was practically at the same level between the groups and amounted to 2.9–3.0 g for light-seeded samples and 2.9–3.1 g for dark-seeded samples.